Studies on neutron spectrum characterization for the Pneumatic Fast Transfer System (PFTS) of KAMINI reactor. (June 2017) - Kumar, G.V.S. Ashok; Sen, Sujoy; Radha, E.; Rao, J.S. Brahmaji; Acharya, R.; Kumar, R.; Venkatasubramani, C.R.; Reddy, A.V.R.; Joseph, M.
Abstract: Characterization of neutron energy spectrum along with the determination of sub-cadmium to epithermal neutron flux ratio ( f ) and the epithermal neutron flux shape factor ( α ) has been carried out at pneumatic fast transfer system (PFTS) of KAMINI reactor. The facility has been extensively used for the neutron activation analysis (NAA) studies using both k0 -NAA and relative method. This paper describes the multi-foil activation method to determine the reaction rates followed by the generation of computed guess spectrum to unfold the neutron spectrum using least square minimization approach. Highlights: Determination of sub-cadmium to epithermal neutron flux ratio & the epithermal neutron flux shape factor. Neutron spectrum characterization using multi-foil irradiation method. High resolution gamma-ray spectrometry for the determination of reaction rates and saturated activities. Generation of guess spectrum using Transport Monte Carlo Code. Neutron spectrum unfolding by least square minimization approach.